Metal/Nonmetal Mill Fires - Maria I. De Rosa (The National Institute for Occupational Safety and Health (NIOSH), 2004)
Table 46 and figure 16 show the number of fires and fire injuries for metal/nonmetal mills by state during 1990-2001. Table 46 also shows the injury risk rates, employees' working hours, and lost workdays. In all, 77 fires occurred in 26 states. Thirty-seven of the fires caused 41 injuries and 1 fatality (including 5 fires and 3 injuries involving contractors). The yearly average was 6.4 fires and 3.4 injuries. Fifty-four fires with 26 injuries and 1 fatality occurred at metal mills; 23 fires with 15 injuries occurred at nonmetal mills. The Ewhr value was 845 x 106 hr (Irr = 0.01), and the LWD value was 6,681. Minnesota had the most fires (16 fires and 5 injuries), followed by Arizona (9 fires and 3 injuries), Wyoming (8 fires and 3 injuries), Nevada (7 fires, 4 injuries, and 1 fatality), and Texas (4 fires and 7 injuries). Of these states, Texas had the highest injury risk rate value (Irr = 0.033). Table 47, partly illustrated in figure 17, shows the number of fires, fire injuries, fire fatalities, risk rates, employees' working hours, and lost workdays by time period. The number of fires increased slightly during the second period, then decreased during the remaining periods. The number of fire injuries show a decrease during most of the periods (an increase is seen during the third period), accompanied by a decline in employees' working hours during most of the periods. The Irr values follow patterns similar to those shown by the injury values. Tables 48-53 show the number of fires by ignition source, method of detection and suppression, equipment involved, location, and burning material by time period. Figure 18 shows the major variables related to fires for 1990-2001. Table 54 shows the number of fire injuries per number of fires causing injuries and total fires by year, ignition source, equipment involved, and location.